THE EFFECT OF ADDITIONAL IRON SAND ON THE CRYSTAL SIZE AND STRAIN OF ZnO - Lorna, Lorna; Mutmainna, Inayatul; Tahir, Dahlang; Gareso, Paulus L (Universitas Mataram, 2022)
This study observed the effect of the addition of iron (Fe) doping on the characteristics of Zinc Oxide (ZnO) nanoparticles.Zn(1-x)Fe(x) with various concentration of x = 0, 2, 4, 6, 8, and 10% was prepared by coprecipitation method using Sodium Hydroxide and Hydrogen Chloride. The effect of adding Fe doping on ZnO was characterized using X-ray Diffraction (XRD) to determine the crystal structure, size, and strain. The analysis result confirmed the absence of additional impurity peaks in the ZnO nanoparticles. Fe doping affects the Zn lattice structure. X-ray diffraction (XRD) study confirms the crystalline Hexagonal structure. Crystal size analysis using Debye Scherrer, UDM, and Halder-Wagner method obtained varying crystal sizes with variations in the concentration of Fe ranging from 19.89-44.72 nm. The crystal size and strain obtained from the Debye Scherrer method are smaller